Management of the Science Laboratory at SMP Negeri 1 Karangnongko in the 2020/2021 Academic Year - Putriardi, Sarahany (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Education units must have laboratory management according to their standards. Laboratories in schools should be guided by standardized laboratories that are in accordance with the national standards of education in Indonesia. The purpose of the study was to determine the description of science laboratory management at SMP Negeri 1 Karangnongko in the 2020/2021 academic year. The research subject is the science laboratory at SMP Negeri 1 Karangnongko in the 2020/2021 academic year. This research is a qualitative descriptive research. Data collection techniques used interviews, observation, and documentation. The instrument used was an observation sheet with a Guttman scale. The validity test was carried out by triangulating data sources which were analyzed using the model from Miles and Huberman with the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the management of science laboratories at SMP Negeri 1 Karangnongko has an average percentage of 53.25% with fairly good criteria, which means that the management of science laboratories at SMP Negeri 1 Karangnongko has not met the standards that have been set, and regulated in the Guidelines for the Management and Utilization of Science Laboratories by the Ministry of Education and Culture in 2017. It is hoped that the results of this study will be an evaluation material that is followed up to improve the quality of the laboratory, so that learning and utilization of science laboratory facilities in schools are carried out optimally and in accordance with the standards.